Detailed Molecular and Immune Marker Profiling of Archival Prostate Cancer Samples Reveals an Inverse Association between TMPRSS2:ERG Fusion Status and Immune Cell Infiltration - Rao, Srinivasa R; Alham, Nasullah K; Upton, Elysia; McIntyre, Stacey; Bryant, Richard J; Cerundolo, Lucia; Bowes, Emma; Jones, Stephanie; Browne, Molly; Mills, Ian; Lamb, Alastair; Tomlinson, Ian; et al. (The Journal of molecular diagnostics : JMD, 2020)
Prostate cancer is a significant global health issue, and limitations to current patient management pathways often result in overtreatment or undertreatment. New ways to stratify patients are urgently needed. We conducted a feasibility study of such novel assessments, looking for associations between genomic changes and lymphocyte infiltration. An innovative workflow using an in-house targeted sequencing panel, immune cell profiling using an image analysis pipeline, RNA sequencing, and exome sequencing in select cases was tested. Gene fusions were profiled by RNA sequencing in 27 of 27 cases, and a significantly higher tumor-infiltrating lymphocyte (TIL) count was noted in tumors without a TMPRSS2:ERG fusion compared with those with the fusion (P = 0.01). Although this finding was not replicated in a larger validation set (n = 436) of The Cancer Genome Atlas images, there was a trend in the same direction. Differential expression analysis of TIL-high and TIL-low tumors revealed the enrichment of both innate and adaptive immune response pathways. Mutations in mismatch repair genes (MLH1 and MSH6 mutations in 1 of 27 cases) were identified. We describe a potential immune escape mechanism in TMPRSS2:ERG fusion-positive tumors. Detailed profiling, as shown herein, can provide novel insights into tumor biology. Likely differences with findings with other cohorts are related to methods used to define region of interest, but this warrants further study in a larger cohort.